Features of upper Dniester oronymy - Осташ, Любов (Geographical names in physical space, 2016)
The village of Stryhantsi of Tysmenytsya District, Ivano-Frankivsk Region is located 30 km northeast of regional centre – city of Ivano-Frankivsk. It is considered to be founded in 1624. The village was mentioned on the map of the French engineer-cartographer Le Vasseur de Beauplan since 1650. Its basic part is located in a wide valley of the right bank of Dniester, 2–3 km of the very river. Local oro-objects are actively included into economic activity of people. Peculiarity of geographical location of the village and agricultural areas lies in the fact that part of them is located in the valley of Dniester, and the other part is located on tops of surrounding mountains which form a single plateau within a certain distance of the village that stretches to the east of the village towards Dniester. Therefore, both generalizing names (Na Hori, Na Dolyni) and specific names as to each separate mountain (na Stintsi, na Serednyomu Horbi, na Hirtsi, nad Zbochem) are used in colloquial speech. Modern oronymy of the village of Stryhantsi and its surroundings (in the language of Stryhantsi residents) is based on folk geographical lexis. Mountains surrounding the village and at the foot of which it is partially located have proper names formed in lexico-semantic way from appellatives which function either in Ukrainian literary language or in dialect speech: Hirka, Zbich, Seredniy Horb, Stinka, Skala. There are no proper names of foreign origin in oronymy of the village of Stryhantsi. Modern oronymy of the village of Stryhantsi and its surroundings is based on folk geographical lexicon. Mountains surrounding the village have their proper names created in lexico-semantic way from appellatives that function either in Ukrainian literary language or in Ukrainian dialect speech: Hirka, Zbich, Seredniy Horb, Skala, Stinka.